Hukum Pembuktian Dalam Perkara Pidana (Perspektif Kemajuan Teknologi Informasi Dan Telekomunikasi) - Aryanto, Moko Dwi; Sudarto, Sudarto (LITERATUS, 2025)
Evidence in Law Number 1 of 2024 concerning the Second Amendment to Law Number I1 of 2008 concerning Electronic Information and Transactions itself is Lex Specialis of the Criminal Procedure Code because it regulates the validity of evidence of criminal acts in cyberspace. In relation to the purpose of criminal procedure law which is to seek material truth, the evidence process is a very decisive stage for judges to obtain confidence in making a decision. The research method is normative juridical. The results of the study are the current legal regulations on evidence in criminal cases in Indonesia, namely regulated in the Criminal Procedure Code, which stipulates the types of valid evidence, principles of evidence, and procedures for evidence to ensure justice and legal certainty and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions which is valid evidence according to law. The development of the evidentiary system in Indonesian criminal law against the advancement of information and telecommunications technology that overall, the development of the evidentiary system in Indonesian criminal law against legal technology reflects efforts to respond to the challenges of the digital era while still upholding the principles of justice. Although still facing various obstacles, the steps that have been taken show that Indonesian criminal law continues to transform to keep up with the times, while maintaining its relevance and effectiveness in law enforcement.